Asymptotic Maturity Behavior of the Term Structure - Klaas Schulze (University of Bonn, Bonn Graduate School of Economics (BGSE), 2008)
Pricing and hedging of long-term interest rate sensitive products require to extrapolate the term structure beyond observable maturities. For the resulting limiting term structure we show two results by postulating no arbitrage in a bond market with infinitely increasing maturities: long zero-bond yields and long forward rates (i) are monotonically increasing and (ii) equal their minimal future value. Both results constrain the asymptotic maturity behavior of stochastic yield curves. They are fairly general and extend beyond semimartingale modeling. Hence our framework embeds arbitrage-free term structure models and imposes restrictions on their specification.
Keywords: G10; G12; E43; 330; bond markets; yield curve; long forward rates; no arbitrage; asymptotic maturity; Rentenmarkt; Zinsstruktur; Laufzeit; Zinstermingeschäft; Kapitalmarkttheorie; Theorie